Dietary Fat Content and Fiber Type Modulate Hind Gut Microbial Community and Metabolic Markers in the Pig - Yan, Hui (Public Library of Science, 2013)
Obesity leads to changes in the gut microbial community which contribute to the metabolic dysregulation in obesity. Dietary fat and fiber affect the caloric density of foods. The impact of dietary fat content and fiber type on the microbial community in the hind gut is unknown. Effect of dietary fat level and fiber type on hindgut microbiota and volatile fatty acid (VFA) profiles was investigated. Expression of metabolic marker genes in the gut, adipose tissue and liver was determined. A 2×2 experiment was conducted in pigs fed at two dietary fat levels (5% or 17.5% swine grease) and two fiber types (4% inulin, fermentable fructo-oligosaccharide or 4% solka floc, non-fermentable cellulose). High fat diets (HFD) resulted in a higher (P<0.05) total body weight gain, feed efficiency and back fat accumulation than the low fat diet. Feeding of inulin, but not solka floc, attenuated (P<0.05) the HFD-induced higher body weight gain and fat mass accumulation. Inulin feeding tended to lead to higher total VFA production in the cecum and resulted in a higher (P<0.05) expression of acyl coA oxidase (ACO), a marker of peroxisomal β-oxidation. Inulin feeding also resulted in lower expression of sterol regulatory element binding protein 1c (SREBP-1c), a marker of lipid anabolism. Bacteria community structure characterized by DGGE analysis of PCR amplified 16S rRNA gene fragments showed that inulin feeding resulted in greater bacterial population richness than solka floc feeding. Cluster analysis of pairwise Dice similarity comparisons of the DGGE profiles showed grouping by fiber type but not the level of dietary fat. Canonical correspondence analysis (CCA) of PCR- DGGE profiles showed that inulin feeding negatively correlated with back fat thickness. This study suggests a strong interplay between dietary fat level and fiber type in determining susceptibility to obesity.